2019
DOI: 10.1029/2019gl084749
|View full text |Cite
|
Sign up to set email alerts
|

Can We Detect Changes in Amazon Forest Structure Using Measurements of the Isotopic Composition of Precipitation?

Abstract: Large-scale (>500 km) spatial gradients of precipitation oxygen isotope ratios (δ 18 O p ) hold information about the hydrological cycle. They result from the interplay between rainout and evapotranspiration along air-parcel paths, but these counteracting effects are difficult to disentangle, complicating quantification of the effect of land cover change on δ 18 O p . We show that disentangling can qualitatively be achieved using climate model simulations with a land-derived precipitation tracer for tropical S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 52 publications
2
8
0
Order By: Relevance
“…Our approach avoids the assumption that upwind moisture loss is constant through time and, as we discuss in the next section, is consistent with evidence that δ 18 O is not always strongly coupled with local precipitation amount (Ward et al., 2019; Wortham et al., 2017). Within our framework, the wettest time occurs when the isotope gradient is steepest, not when central δ 18 O is lowest, consistent with our understanding of how Δδ 18 O relates to precipitation today (Ampuero et al., 2020; Pattnayak et al., 2019; Salati et al., 1979).…”
Section: Discussionsupporting
confidence: 85%
“…Our approach avoids the assumption that upwind moisture loss is constant through time and, as we discuss in the next section, is consistent with evidence that δ 18 O is not always strongly coupled with local precipitation amount (Ward et al., 2019; Wortham et al., 2017). Within our framework, the wettest time occurs when the isotope gradient is steepest, not when central δ 18 O is lowest, consistent with our understanding of how Δδ 18 O relates to precipitation today (Ampuero et al., 2020; Pattnayak et al., 2019; Salati et al., 1979).…”
Section: Discussionsupporting
confidence: 85%
“…Subcloud evaporation, which is more likely in the winter when the atmosphere is drier, may also play a role in the higher winter d‐excess p values if precipitation condenses from reevaporated vapor (e.g., Risi et al., 2008). Evapotranspiration from the Amazon Basin may amplify this d‐excess p seasonality if the bare‐ground evaporation flux increases during the dry season (Pattnayak et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Barichivich et al [33] found an intensification of Walker's circulation during the late 1990s, associated with strong warming of the tropical Atlantic and cooling of the tropical Pacific. Furthermore, Pattnayak et al [34,35] analyzed the relationship of precipitation in northern and northwestern South America with SST anomalies in the Atlantic after 2000. Therefore, through these interbasin SST gradients, the PDO and AMO SST mean states modulated the CJ and CLLJ variations during the last three decades [30].…”
Section: Of 18mentioning
confidence: 99%